Spanish captives run away from Constantinople in the XVIth century - González Castrillo, Ricardo (Anaquel de Estudios Árabes, 2011)
In the XVIth century, it took place an important number of captures of spanish people by turkish corsairs due to strikes along the Mediterranean coast or for military actions. Unfortunately, we can't know how much people have been prisoners but this amount had to be high. The destination of these captives was, on the one hand, the city of Constantinople itself and, on the other, several countries of North Africa, such as Argel, Tunis and Tripoli. In Constantinople, they had a better treatment and much more possibilities to run away but it was true that their options to be rescued were limited. Most of them selected to refuse the christian faith and, for this reason, they converted into muslims and the number of renegades who lived in the ottoman empire was numerous. This article deals with different stories of captives in the city of Constantinople and their flights from this, through the study of an important number of manuscripts that they belongs to collections of the General Archive of Simancas and Libraries, such as National Library of Spain, El Escorial Monastery and Royal Academy of History (Madrid). In the whole cases, the flights are in group, with more o less number of escapees, that reached their freedom. A few of them wrote and autobiographical book in which they related the experiences of their captivity although this fact wasn't very common.
Keywords: Early Modern Age; XVIth century; captives; Constantinople; North Africa; renegades.